Estudo sobre: fatores sociodemográficos maternos e obstétricos associados à via de parto em participantes do projeto viver - Gabira, Fernanda Garcia (2023)
In recent years, Brazil has had one of the highest cesarean section rates in the world and is always remembered as an example of the excessive use of the procedure. Compared to the rest of the country, cesarean section rates are equally high in the state of Espírito Santo. Therefore, the objective of this study is to evaluate sociodemographic and obstetric factors about the mode of delivery among participants of the Projeto Viver in maternity hospitals in the state of Espírito Santo. The Projeto Viver is a multicenter cohort study whose main objective was to investigate the influence of early determinants of morbidity in the perinatal and neonatal periods of children born in Espírito Santo - Brazil. The Projeto Viver was carried out from August 2019 to March 2020 in three maternity hospitals located in the metropolitan region and north of the state. 3,438 postpartum women and their newborns participated in the research, which consisted of three monitoring stages. The results of this thesis were described in three articles. The first manuscript aimed to identify sociodemographic factors associated with the mode of delivery through a systematic review. The results show that in the last six years, sociodemographic factors continue to influence the type of birth performed, women with a higher socioeconomic level, higher level of education, aged over 35 years, and giving birth in private institutions have a greater chance of having a cesarean section compared to childbirth vaginal. The second article used data from Projeto Viver and aimed to evaluate the sociodemographic, maternal, and gestational factors associated with cesarean sections in Projeto Viver participants. A prevalence of cesarean section was found to be 57.4% of all births, with a higher incidence of cesarean section in women aged ≥35 years (74.5%), in those with an education level of ≥12 years (64.1%), in those belonging to the highest socioeconomic quintile (72.2%) and who gave birth in private hospitals (73.7%). There was a higher prevalence of cesarean section births among women aged 25 or over, with a higher educational level, with obesity and chronic non-communicable diseases, and a lower frequency among those who gave birth in philanthropic hospitals. Finally, a third article evaluated obstetric complications and their association with the mode of delivery among women from Projeto Viver. The results demonstrate that there is a higher proportion of complications in women aged 35 years or over, who belong to the last wealth quintile, with a higher level of education and in private maternity hospitals, as well as in those with obesity and with a gestational age <37 weeks. Regarding the association between obstetric complications due to the route of delivery, we found that women who had fetal distress, amniotic fluid disorders, diabetes mellitus pregnancy, and hypertensive syndrome had a higher prevalence of cesarean sections compared to those without the complications mentioned above. It is concluded throughout this thesis that factors recognized in the literature are present in the studied population. The results presented here are relevant as they have the potential to contribute to the scientific literature and the evaluation of implementations and policies that are in force in the state's maternity hospitals so that strategies can be improved in search of reducing cesarean sections.